Advances in the classification of primary systemic vasculitis - Suppiah, R; Basu, N; Watts, R; Luqmani, R (2009)
The primary systemic vasculitides are a heterogeneous group of diseases with inflammation of blood vessels being the defining common characteristic. Classification criteria and disease definitions are important for clinical studies and therapeutic trials, but have a very limited role in clinical practice. The purpose of classification criteria is to differentiate between different types of vasculitis once a diagnosis of vasculitis has been made. Classification criteria in vasculitis are used to group together patients with similar or identical conditions. The current classification schema for vasculitis takes into consideration clinical and histological features plus the dominant vessel size. This review takes a critical look at the current state of classification criteria for primary systemic vasculitis including the American College of Rheumatology 1990 criteria, the Chapel Hill Consensus Conference definitions, and the European Medicines Agency Algorithm - which has been a way of addressing the discrepancies between the two systems. With the deficiencies in the current criteria, we advocate the need for improvement and validation of existing classification criteria, together with an attempt to formulate validated diagnostic criteria in this uncommon but important group of diseases.